2011
DOI: 10.1111/j.1095-8312.2011.01715.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological convergence during pregnancy among predator and nonpredator populations of the livebearing fishBrachyrhaphis rhabdophora(Teleostei: Poeciliidae)

Abstract: Predation can drive morphological divergence in prey populations, although examples of divergent selection are typically limited to nonreproductive individuals. In livebearing females, shape often changes drastically during pregnancy, reducing speed and mobility and enhancing susceptibility to predation. In the present study, we document morphological divergence among populations of nonreproductive female livebearing fish (Brachyrhaphis rhabdophora) in predator and nonpredator environments. We then test the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 26 publications
0
66
0
Order By: Relevance
“…Our analytical framework enabled us to consider the interplay of multivariate variation in several character suites. For example, body-shape divergence between predator regimes in females might reflect a trade-off between selection on locomotion and selection on reproduction818283. Selection might act primarily on reproductive traits (fecundity, RA) that indirectly affect body shape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analytical framework enabled us to consider the interplay of multivariate variation in several character suites. For example, body-shape divergence between predator regimes in females might reflect a trade-off between selection on locomotion and selection on reproduction818283. Selection might act primarily on reproductive traits (fecundity, RA) that indirectly affect body shape.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observation of how life histories might influence body shape were made in other studies on livebearing fishes. For example, Wesner et al 83. demonstrated that body shape differences between high- and low-predation populations of B. rhabdophora largely disappear in gravid females, while two other recent studies showed that high RA negatively affects swimming performance and predator escape responses in guppies8184, and thus results in a change in habitat use to compensate for this constraint on swimming performance84.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis has been used previously and effectively in another Brachyrhaphis species [6]. The PCVA tests whether the significant interaction between main effects and the index variable resulted from differences in magnitude ( MD ) or direction (Θ) of morphological change.…”
Section: Methodsmentioning
confidence: 99%
“…In a multivariate mixed model design, relative warps are treated as repeated measures within individuals, thus individual is treated as a random variable in the analysis. Analysis was done with the MIXED procedure in SAS (SAS Enterprise Guide v. 4.3, SAS Institute Inc., Cary, NC, USA) [29,30].…”
Section: Methodsmentioning
confidence: 99%